Efektivitas Jumlah Lubang Pada Tabung Pembakaran Terhadap Performa Kompor Biomassa - Susi Rahayu; Habib Ridwansyah; Dian Wijaya Kurniawidi; I G N Yudi Handayana; Siti Alaa`; Arif Budianto (Universitas Hamzanwadi, 2024)
Global energy requirements encourage innovations in developing environmentally friendly alternative energy sources by transforming biomass waste into biopellets. The use of biopellets as fuel was followed by the development of biomass stoves for households. Developing biomass stove technology design is essential, so this research aims to design a biomass stove with good performance for use as a household stove. Stove performance was identified by reviewing the biomass stove's fuel consumption and thermal efficiency relative to the number of combustion holes. The biomass stove fabrication results had been successfully created based on a stove design using galvanized plate material. The design focused on three layers of tubes, including the stove frame, the air supply control, and the combustion tube. The number of holes in the combustion tube affected fuel consumption and the thermal effectiveness of the stove. The lowest fuel consumption on a furnace with six combustion holes was 2,306 kg/hour. Meanwhile, the optimal thermal efficiency for burning 18 holes was 16.17%. However, this thermal efficiency value needs to meet the SNI 7926: 2013 standard. The location and number of combustion holes in the combustion tube could influence the performance of the biomass stove. Therefore, it is important to modify biomass stoves to fulfill SNI standards.